THE EFFECTS OF STOCKING DENSITY AND THE GIVING TOFU WITH DIFFERENT DOSES ON THE POPULATION GROWTH SILK WORMS ( Tubifex sp) - Reza Ahmad; Nuraini '; Sukendi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on March - May 2016 in the Jln . Kamboja No. 38 , Simpang Baru , Pekanbaru Panam . This research aimed to determine the stocking density and feeding tofu dose is right for biomass growth , population and the length of silk worms ( Tubifex sp ) . The method used in this study is an experiment using a completely randomized design factorial 2 factors 3 levels of treatment with three replications . The first factor stocking density ( 35 g , 45 g and 55 g ) and doses of the feed tofu ( 35 g , 45 g , 55 g ) . The results showed that the stocking density and feeding tofu significant effect on biomass ( p < 0.05 ) . Values of biomass , length growth , and the population is highest in the treatment of stocking density 55 g / 0.098 m2 and dose feed 55 g of biomass 152g / 0.098 m2 , length growth of 1.2 cm , 19 765 ind / 0.098 m2.Key word:Tubifex sp,Stocking Density, Doses of Feed, Population Growth, Silk Worm